Corporate Governance and Corporate Social Responsibility Disclosure - Jizi, Mohammad Issam (2014)
There is a distinct lack of research into the relationship between corporate governance and corporate social responsibility (CSR) in the banking sector. This paper fills the gap in the literature by examining the impact of corporate governance, with particular reference to the role of board of directors, on the quality of CSR disclosure in US listed banks’ annual reports after the US sub-prime mortgage crisis. Using a sample of large US commercial banks for the period 2009–2011 and controlling for audit committee characteristics, board meeting frequency, and banks’ profitability, size and risk, we find evidence that board independence and board size, the two board characteristics usually associated with the protection of shareholder interests, are positively related to CSR disclosure. This indicates that, with regard to CSR disclosure, more independent boards of directors and larger boards are the internal corporate governance mechanisms which promote both shareholders’ and other stakeholders’ interests. Contrary to our expectations, CEO duality also impacts positively on CSR disclosure. From an agency-theoretical viewpoint, this suggests that powerful CEOs may promote transparency about banks’ CSR activities for their private benefits. While this could indicate that powerful CEOs are under particular pressure to appease stakeholders’ concerns that they might abuse their power by providing a high degree of CSR disclosure, it could also be a sign of managerial risk aversion or managers’ private reputational concerns.